La nuova rete GNSS multicostellazione dell’Umbria - Fabio Radicioni; Aurelio Stoppini (GEOmedia, 2019)
The GPSUMBRIA permanent station network (Umbria region, central Italy), renewed in all its components, is the first GNSS network in Italy and among the first in the world to provide positioning services on four constellations (GPS, GLONASS, GALILEO and BEIDOU). It is now possible to access more than 30 satellites at the same time, with considerable advantages for the users, especially in critical areas with presence of obstructions. Positioning services have also been revised and optimized to support a wider spectrum of activities and a number of users greatly expanded thanks to the diffusion and functionality improvement of the mobile devices.